Granulocyte-macrophage colony-stimulating factor (GM-CSF) in subjects with different stages of periodontitis according to the new classification - Dikilitas, Ahu; Karaaslan, Fatih; Aydin, Esra Özge; Yigit, Umut; Ertugrul, Abdullah Seckin (Journal of applied oral science, 2022)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a multifunctional cytokine that regulates inflammatory responses in various autoimmune and inflammatory disorders. The purpose of this study was to analyze the gingival crevicular fluid (GCF) for GM-CSF, interleukin-1 beta (IL-1β), and macrophage inflammatory protein-1 alpha (MIP-1α) levels in patients with stage I, stage II, stage III, and stage IV periodontitis (SI-P, SII-P, SIII-P, and SIV-P). A total of 126 individuals were recruited for this study, including 21 periodontal healthy (PH), 21 gingivitis (G), 21 SI-P, 21 SII-P, 21 SIII-P, and 21 SIV-P patients. Plaque index (PI), gingival index (GI), presence of bleeding on probing (BOP), probing depth (PD), and attachment loss (AL) were used during the clinical periodontal assessment. GCF samples were obtained and analyzed by an enzyme-linked immunosorbent assay (ELISA). GCF GM-CSF, MIP-1α, and IL-1β were significantly higher in SII-P and SIII-P groups than in PH, G, and SI-P groups (p<0.05). There was no significant difference among the PH, G, and SI-P groups in IL-1β, GM-CSF, and MIP-1α levels (p>0.05). These results show that GM-CSF expression was increased in SII-P, SIII-P, and SIV-P. Furthermore, GM-CSF levels may have some potential to discriminate between early and advanced stages of periodontitis.